1995
DOI: 10.1063/1.470444
|View full text |Cite
|
Sign up to set email alerts
|

A thermodynamic investigation of dynamical disorder in Phase II of CBr4

Abstract: CBr 4 is an archetypal example of a pseudospherical molecule that can form an orientationally disordered phase ͑phase I, 320 KϽTϽ365 K͒. At lower temperatures, phase II is the stable phase; although it must be more ordered than phase I, different techniques give conflicting results concerning order in phase II. In order to investigate dynamical disorder in phase II, the heat capacity of CBr 4 has been measured in the temperature range 30-305 K. No phase transitions were found in this region. The calculated hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Comparing the new results to those of earlier studies on the disordered phase, the previously observed streak system was qualitatively reproduced, although the distribution of bromine atoms was close to random in the coordinate system of the lattice. For the ordered phase distinct equilibrium positions but significant thermal displacements were found, explaining the disordered character noticed earlier for this phase . Turning to the real space behavior, the most striking point was that “...positional correlations are nearly identical in the plastic crystalline and the liquid phases...” in terms of the bromine–bromine PRDF (Figure ).…”
Section: Liquids Of Perfect Tetrahedral Moleculesmentioning
confidence: 62%
See 1 more Smart Citation
“…Comparing the new results to those of earlier studies on the disordered phase, the previously observed streak system was qualitatively reproduced, although the distribution of bromine atoms was close to random in the coordinate system of the lattice. For the ordered phase distinct equilibrium positions but significant thermal displacements were found, explaining the disordered character noticed earlier for this phase . Turning to the real space behavior, the most striking point was that “...positional correlations are nearly identical in the plastic crystalline and the liquid phases...” in terms of the bromine–bromine PRDF (Figure ).…”
Section: Liquids Of Perfect Tetrahedral Moleculesmentioning
confidence: 62%
“…For the ordered phase distinct equilibrium positions but significant thermal displacements were found, explaining the disordered character noticed earlier for this phase. 289 Turning to the real space behavior, the most striking point was that "...positional correlations are nearly identical in the plastic crystalline and the liquid phases..." in terms of the bromine− bromine PRDF (Figure 7). This way the steric effects have been identified as the main reason for orientational correlations.…”
mentioning
confidence: 99%
“…The ordered phase has been studied in relation to the order-disorder transition and in comparison with similar materials, using diraction methods 1,9,16,17 , measurements of thermodynamic parameters 18 and via molecular dynamics simulations 19 . The structure is a distorted face centered cubic one, which could eventually be rened as monoclinic 1 .…”
Section: Introductionmentioning
confidence: 99%
“…, thermal expansion and conductivity and melting) . The Grüneisen parameter, as defined by thermodynamic variables (γ = α V VB / C where α V is the thermal expansion and C is the isobaric heat capacity), has been a useful concept aiding understanding of anharmonicity. , The overall Grüneisen parameter can be directly related to lattice dynamics and energetics through its modal counterparts 3 (γ i = −∂ ln ω i /∂ ln V ). This concept has been extended to elucidate even more clearly the subtleties of the interplay between the lattice dynamics and the thermal expansion as well as the degree of anharmonicity in, and the coupling between, lattice modes in anisotropic materials …”
Section: Grüneisen Parametersmentioning
confidence: 99%